Pemanfaatan Metode PECS (Picture Exchange Communication System) untuk Meningkatkan Pemahaman Instruksi Dua Langkah pada Peserta Didik Autis Spektrum Disorder - Pinky Agustin, Madeline; Kinanthi , Morula; Mauliya; Ananda , Eka; Ardianingsih, Febrita; Wahyudi, Zahra Ajid Berlianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the use of the Picture Exchange Communication System (PECS) method to enhance the understanding of two-step instructions among learners with Autism Spectrum Disorder (ASD). The aim of this research is to provide a comprehensive explanation of the application of PECS as a method to improve communication skills and the ability to follow two-step instructions in children diagnosed with ASD. A descriptive qualitative approach was employed, with data collected through direct observation, interviews, and documentation at Sonokwijenan II/96 Surabaya State Elementary School. The results indicate that the use of PECS is effective in improving students’ ability to comprehend sequential two-step instructions and express their needs.